Atrial Septal Aneurysm in Young and Middle Age Patients with A New Paroxysm of Atrial Fibrillation in Babylon Province (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background and Objectives:  Atrial fibrillation is one of the  most common atrial arrhythmia , it may be associated with alote of structural and  functional cardiac causes . The Aim of this study was to evaluate a possible causal relationship between ASA ( atrial septal aneurysm ) and the occurrence of paroxysmal AF in young and middle age patients , and reporting of  some other structural and pathological abnormality diagnosed by standard transthoracic echocardiography. Design and Methods: This study was involved  young and middle age groups (20-55 years), itincluded 339 patients with new paroxysmal atrial fibrillation , but 37 of them was excluded from the study, (male 250 and female 52) with additional 300 control group. All patients were examined By standard transthoracic echocardiographic  protochol that involve two dimension ( 2D) , M-Mood and dopplar , looking for possible cardiac structural causes for the  new onset  paroxysmal atrial fibrillation and special attention was made to the inter atrial septum. The Results: The paroxysmal atrial fibrillation is more with 41-55 years age group that represents 65.56% of patients , while the age group  20-40 years which give 34.44%. The paroxysmal atrial fibrillation is  more in male group (82.78%), than  female group ( 17.22%) . The paroxysmal atrial fibrillation patients show many associated heart abnormalities (acquired and congenital diseases) by echocardiographic results, and specifically, the ASA is 17.21% in AF patients. The highest percentage of  ASA are 21.2% in the age group 41-55 years old, and 18.4% in male group, with significant relationship between them(P value < 0.05, odds ratio is 12.3, chi-square is 42.64 , 95% confidence interval 4.8-31.19). Conclusion: Echocardiography has a significant  role  in the  diagnosis of  causes of AF. There is a strong association of ASA and the onset of new paroxysmal AF, More for those patients older than 41 years old , more in male than female.